Structure and dynamics of the gammaM4 transmembrane domain of the acetylcholine receptor in lipid bilayers: insights into receptor assembly and function. - De Almeida, R; Loura, L; Prieto, M; Watts, A; Fedorov, A; Barrantes, F (2006)
A 28-mer peptide (gammaM4) corresponding to the fourth transmembrane segment of the nicotinic acetylcholine receptor (AChR) gamma-subunit, with a single tryptophan residue (Trp6), was reconstituted into lipid bilayers of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), loaded with either high or low amounts of cholesterol, i.e., in the conjugated liquid-ordered and liquid-disordered phases, respectively, at room temperature. By making use of the Trp intrinsic fluorescence, both steady-state and time-resolved fluorescence techniques were employed, namely, red-edge excitation shift effect, decay-associated spectra (DAS), and time-resolved anisotropy. The results obtained here, together with previous studies on the same reconstituted peptide, indicate that: (i) Trp6 is strongly anchored in the bilayer with a defined transverse location; (ii) the modifications in the measured DAS are related to the complex result of a self-quenching process on the decay parameters; (iii) the wobbling movement of the indole moiety of Trp6 is fast but severely restricted in amplitude; and, (iv) in the liquid-ordered phase, the bilayer properties and the tilt angle of the peptide enhance peptide-peptide interactions, with the formation of peptide rich patches and possibly some anti-parallel helix-helix aggregates, showing different dynamics from that of the peptide in the liquid-disordered phase where the peptide is randomly distributed.